IMPLEMENTASI REWARD PADA PRAKTEK PEMBELAJARAN PAI DI TPA NURUL YAQIN DESA BANYU HIRANG KECAMATAN AMUNTAI SELATAN - Susanti, Ria; Azmi, Falhi; Maulana, M Aditya; Noorfadillah, Muhammad; Amalia, Fitria; Isabella, Isabella (STIT Ibnu Rusyd Tanah Grogot, 2022)
One method and learning strategy that is often used and very effective in stimulating and fostering enthusiasm and motivation for learning is giving rewards. Reward in the world of education and Islam means tsawab/pahala/reward. Rewards are the result of good deeds given by God. And the word